Water And The Flint Hills - Rex Buchanan; Bob Sawin (Symphony in the Flint Hills, 2010)
Nobody wants rain tonight. But ask yourself, If rain fell here, where would it go? To truly understand a place, you must know something about its water. That’s true for all of Kansas, and it’s certainly true for the Flint Hills.
Keywords: water; conservation; water table; rain; movement; erosion; hillside; pasture; grassland; prairie; grass; plant; Cottonwood River; limestone; springs; Chase County; Diamond creek; Neosho River; Walnut River; Kansas River; stream; flow; topographic; headwaters; dry; drought; shortage; water cycle